Organizational self evaluation with integration of management models - Molnár, Viktor (НТУ "ХПИ", 2011)
The paper points some problems of the separated used management models and try to lighten the necessity of parallel using of these models. The major gap of it is the realization of connections among the models. I introduce an existing integrated management model which is applied succesfully at some firms and non-profit organizations. My work is the development of the model referring to the above mentioned connections among its subsystems. The validation of the basic model is given but the developed variation was not tested yet in practise. The conceptual structure and the logic referring to the process of use is correct.